Applications of MRI sequences in perianal and luminal Crohn’s disease - Alyami, Ali (2020)
Magnetic resonance imaging (MRI) is a non-invasive imaging method which was discovered as the magnetic resonance phenomenon or nuclear magnetic resonance by Felix Bloch and Edward Purcell in 1946. It had long been used to study molecular structure and diffusion in the fields of chemistry and physics. Currently, the primary use of clinical MRI is in imaging anatomy, body pathology, and is used to assess organ function. In combination with the transmission and detection of radio waves, MRI uses a high magnetic field to produce images of the body from MR signals. Also, MRI offers a variety of techniques and measurable physical parameters for sensitising the image. This thesis focuses on using MRI in abdominal imaging and in clinical applications. The focus of this thesis is on the use of MRI in abdominal and peri-anal clinical applications in Crohn’s disease in particular. Many studies have been conducted on human or animal abdominal organs in various areas of research, both in basic experimental and in clinical applications. This thesis focuses on the performance of MRI sequences in areas, such as, magnetisation transfer (MT), T2 relaxometry, diffusion-weighted imaging (DWI), and dynamic contrast enhancement (DCE), in evaluating treatment response in Crohn's disease (CD) and its complications (perianal disease location). Several aspects have been examined: the possibility of assessing therapy response, the correlation among these sequences, also with clinical indexes, and the repeatability of different MRI features. DWI is a modality of imaging that enables tissue microenvironment characterisation through the measurement of variations in water molecules' mobility. These variations are typically the result of several factors, including water molecule compartments (intracellular or extracellular spaces, intravascular), cell membranes, and depend on changes in the tissue structure that alter under certain inflammatory processes. DCE visualises the weighted intensity of the T1 signal over time following an intravenous contrast injection. These curves of time-intensity can provide various quantitative measurements of disease activity and assessments of treatment response in CD5. In a quantitative assessment, T1 and T2 relaxation times can also provide estimates of total water content in the tissue. The tissue's properties and the amount of water within may dramatically change with injury and disease. Pathology, such as inflammation, is associated with accumulation of water in the intra-extracellular spaces, thereby affecting T1 and T2 relaxation times. MT suggests the possibility of quantifying intestinal fibrosis through non-invasive determination of tissue collagen in CD.